2001
DOI: 10.2337/diacare.24.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glycemic Control by 1 Year of Insulin Therapy Leads to a Sustained Decrease in sE-Selectin Concentrations in Type 2 Diabetes

Abstract: OBJECTIVE -To examine whether and how improvement of glycemic control by long-term insulin therapy decreases endothelial activation as measured by serum levels of the soluble adhesion molecules sE-selectin and vascular cell adhesion molecule (VCAM-1) and whether the drug used to lower blood glucose in addition to insulin influences such a response.RESEARCH DESIGN AND METHODS -Circulating adhesion molecules were measured before and after 3 and 12 months of therapy in 81 patients with type 2 diabetes and 41 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
7
23
1
Order By: Relevance
“…In fact, several CVD biomarkers (e.g. TNF-a, adhesion molecules, vWf, t-PA-ag and PAI-1-ag) have been associated with phenotypes of the metabolic syndrome (16)(17)(18). From the present study, we have previously reported a non-significant difference in levels of HbA 1c (0.17 percentage points), significantly lower body weight (1.58 kg) and significantly lower fasting serum insulin levels (13%) during metformin than repaglinide treatments (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, several CVD biomarkers (e.g. TNF-a, adhesion molecules, vWf, t-PA-ag and PAI-1-ag) have been associated with phenotypes of the metabolic syndrome (16)(17)(18). From the present study, we have previously reported a non-significant difference in levels of HbA 1c (0.17 percentage points), significantly lower body weight (1.58 kg) and significantly lower fasting serum insulin levels (13%) during metformin than repaglinide treatments (33).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we collectively term these non-conventional CVD risk markers 'CVD biomarkers'. Interrelations between the CVD biomarkers and the glycaemic variables have been suggested (16)(17)(18). Thus, biological mechanisms both dependent and independent of glycaemia might influence the CVD biomarkers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Efficacy in special populations Weight Metformin is widely recognised to have either little effect on body weight or to facilitate modest weight loss in type 2 diabetes. 69 There is no major effect of obesity status on the antihyperglycaemic effect of metformin but a slightly larger glucose-lowering effect of metformin has been observed as body mass index (BMI) decreases.…”
Section: Metformin In Combinationmentioning
confidence: 99%
“…Additionally, only serum VCAM-1 was measured, which may be less sensitive than other soluble CAMs in predicting in vivo endothelial dysfunction. [23] This could partly explain the lack of signiÞ cant changes in the VCAM-1 levels despite signiÞ cant improvements in glycemic control and peroneal nerve function following treatment.…”
Section: Journal Of Medical Sciencesmentioning
confidence: 89%